2020
DOI: 10.1038/s41598-019-57159-3
|View full text |Cite
|
Sign up to set email alerts
|

D-tyrosine adds an anti-melanogenic effect to cosmetic peptides

Abstract: D-tyrosine is known to negatively regulate melanin synthesis by inhibiting tyrosinase activity. Here, we further reveal that peptides containing terminal D-tyrosine can reduce the melanin contents of human melanocytes. the addition of D-tyrosine to the terminus of the commercial anti-wrinkle peptide, pentapeptide-18 endowed the peptide with the ability to reduce the melanin content and tyrosinase activity in human MNT-1 melanoma cells and primary melanocytes. Consistently, terminal D-tyrosine-containing pentap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Then, successive chemical reactions are triggered until melanin is completely formed [ 11 , 12 ]. Due to its determinant role in the biosynthetic pathway of melanin, tyrosinase has been widely investigated as an interesting molecular target with applications in the pharmaceutical and cosmetic industries [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, successive chemical reactions are triggered until melanin is completely formed [ 11 , 12 ]. Due to its determinant role in the biosynthetic pathway of melanin, tyrosinase has been widely investigated as an interesting molecular target with applications in the pharmaceutical and cosmetic industries [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…D-Tyrosine has no established activity in the brain but has recently been shown to be effective as a tyrosinase inhibitor, preventing melanin formation [ 22 , 56 ]. This is particularly interesting as tyrosinase has been implicated in neurodegenerative diseases such as Parkinson’s Disease [ 126 , 127 ].…”
Section: Neuroactive D-isomers Without Direct Nmda Receptor Interamentioning
confidence: 99%
“…Treatment with 10 mM D -Tyr reduced melanin synthesis in the epidermal basal layer of a 3D human skin model [ 92 ]. In a subsequent study, this research group demonstrated that the addition of a D -Tyr residue to the C-terminus of certain functional peptides could increase their TYR inhibitory activity in vitro and antimelanogenic activity in cells, while retaining the intrinsic properties of the unmodified peptides [ 93 ].…”
Section: Artificial Downregulation Of Melanin Synthesismentioning
confidence: 99%